Kajian Teknis Flyrock Dan Jarak Aman Minimum Peledakan Di Jobsite PT Unggul Dinamika Utama Site PT Indexim Coalindo: Flyrock Technical Study and Minimum Safe Distance for Blasting at PT Unggul Dinamika Utama's Jobsite at PT Indexim Coalindo's Site - Indra, M Alfarie; Franto; Guskarnali (MINERAL, 2025)
This study examines the condition of flyrock and safe blasting distance at the jobsite of PT Unggul Dinamika Utama-PT Indexim Coalindo in East Kutai, East Kalimantan. The study was conducted at Pit Tempudo 6 by collecting blasting geometry data and actual flyrock points using GPS as many as 30. The research method used was the actual calculation of flyrock throwing distance using Pythagoras and the predicted calculation of flyrock throwing distance using the theory of Richard and Moore and Ebrahim Ghasemi which was then carried out a technical study of flyrock and minimum safe blasting distance. The processing results showed the use of an average blasting geometry with a burden value of 7.86m, spacing of 8.96m, stemming of 3.64m, blast hole depth of 7.05m, powder column of 81.64kg with the furthest actual flyrock distance of 90.3m. The influence of blasting geometry parameters obtained a burden value of 0.01%, spacing of 0.86%, Stemming of 18.09%, blast hole depth of 6.38%, powder column of 2.21%. Stemming has a high influence on flyrock, with a percentage of 18.09%. Additional factors such as inadequate site preparation and insufficiently dense stemming also contribute to flyrock. Theoretical predictions after the calculated data were transformed showed that the Richard and Moore cratering factor method had the closest results, at 24%, compared to Ebrahim Ghasemi's 29%. Based on technical studies, the recommended safe radius is 181 m for heavy equipment, while for humans it remains at 500 m.